2023
DOI: 10.1093/europace/euad020
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive stereotactic arrhythmia radiotherapy for ventricular tachycardia: results of the prospective STARNL-1 trial

Abstract: Aims Stereotactic arrhythmia radiotherapy (STAR) is suggested as potentially effective and safe treatment for patients with therapy-refractory ventricular tachycardia (VT). However, the current prospective knowledge base and experience with STAR is limited. In this study we aimed to prospectively evaluate the efficacy and safety of STAR. Methods and results The StereoTactic Arrhythmia Radiotherapy in the Netherlands no.1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…It was first introduced in 2012 [96] as a treatment for patients with frequent VT recurrences after catheter ablation and appropriate antiarrhythmic treatment and showed promising short-term results [96][97][98][99][100][101][102][103][104], although further recurrences proved to be quite frequent [105][106][107].…”
Section: Stereotactic Arrhythmia Radioablation or Radiotherapy Ablationmentioning
confidence: 99%
“…It was first introduced in 2012 [96] as a treatment for patients with frequent VT recurrences after catheter ablation and appropriate antiarrhythmic treatment and showed promising short-term results [96][97][98][99][100][101][102][103][104], although further recurrences proved to be quite frequent [105][106][107].…”
Section: Stereotactic Arrhythmia Radioablation or Radiotherapy Ablationmentioning
confidence: 99%
“…During the follow-up period, no treatment-related serious adverse events were observed. 15 In addition, scientists have also proposed the use of proton beams, carbon beams, and other energies for VT ablation, 16 but these non-invasive VT ablation methods require further studies on the long-term efficacy and potential effects of radiation on the heart and adjacent organs are still under investigation. Pulsed field ablation (PFA) is a novel, non-thermal modality by irreversibly electroporating cell membranes, which can spare collateral tissues damage.…”
Section: Alternative Energymentioning
confidence: 99%
“…Meta-analysis of seven observational studies with a total of 61 patients showed that six months after STAR, the VT burden reduction was 92%, accompanied with an 86% reduction in the number of ICD shocks [62]. Several small prospective trials were recently published [63][64][65][66][67]. These studies primarily focused on safety and indicated that STAR has acceptable short-term toxicity with no significant concerns regarding acute cardiac toxicity.…”
Section: Management Of Ventricular Arrhythmias In Lung Cancer Patientsmentioning
confidence: 99%